Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.7556/jaoa.2020.158
|View full text |Cite
|
Sign up to set email alerts
|

Toward Resilience: Medical Students' Perception of Social Support

Abstract: Context: There is strong evidence that social support-particularly perceived social supportfunctions as a protective factor for health. Few studies have investigated how medical students perceive the types of social support they experience. Objective: To determine how osteopathic medical students perceive social support, understand the factors that influence their perceptions, and explore how group participation in a cocurricular, academic program could affect student perceptions. Methods: In this cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 39 publications
(47 reference statements)
0
17
0
Order By: Relevance
“…Social support was also correlated and negatively predicted anxiety (Jahan et al, 2016). Moreover, in the context of medical education, previous study has found that there is a strong correlation between group membership and well-being (Casapulla et al, 2020). Empirical studies also indicated social support and mental health are closely related (Peng et al, 2012).…”
Section: Anxiety As a Mediating Rolementioning
confidence: 97%
“…Social support was also correlated and negatively predicted anxiety (Jahan et al, 2016). Moreover, in the context of medical education, previous study has found that there is a strong correlation between group membership and well-being (Casapulla et al, 2020). Empirical studies also indicated social support and mental health are closely related (Peng et al, 2012).…”
Section: Anxiety As a Mediating Rolementioning
confidence: 97%
“…In contrast, however, Zamani-Alavijeh et al ( 2017 ) found that over 60% of medical science students in Iran ( n = 763) reported low levels of social support, with females reporting significantly lower levels than male students. These findings suggest that males and female students may have different support needs, but also may perceive source social support differently (Casapulla et al, 2020 ; Zamani-Alavijeh et al, 2017 ). While there is a significant body of research developing in this area of studies, they vary significantly in methodology, definition of social support, timing of data collected, population samples, cultural differences and students’ living circumstances, making it difficult to make direct comparisons across studies on the levels of social support available to students.…”
Section: Social Support and Stressmentioning
confidence: 97%
“…Family support has consistently been identified as playing an important role in academic persistence (Abukari, 2010 ; Nelson, 2019 ; Sosu & Pheunpha, 2019 ; Theodore et al, 2017 ), while support derived from peers and support groups is associated with positive academic outcomes (Kim et al, 2017 ; Li et al, 2018a , b ), including enhancing understanding of course materials and clarifying difficult concepts (Collins et al, 2010 ; Gallop & Bastien, 2016 ; Masserini & Bini, 2021 ). In terms of other sources of support, while students may access support from academic staff to a lesser extent than that from other sources (Blair, 2017 ; Casapulla et al, 2020 ; Reeve et al, 2013 ), these relationships are found to be important for both wellbeing and transition to university (Cage et al, 2021 ; Jun et al, 2018 ; Maymon et al, 2019 ; Meehan & Howells, 2017 ; Reeve et al, 2013 ). Research has identified that certain programmes due to teaching methods and small group classes may lead to greater peer social support (Jun et al, 2018 ).…”
Section: Social Supportmentioning
confidence: 99%
See 2 more Smart Citations